G2013 modulates TLR4 signaling pathway in IRAK-1 and TARF-6 dependent and miR-146a independent manner - Hajivalili, M; Pourgholi, F; Majidi, J; Aghebati-Maleki, L; Movassaghpour, A A; Samadi Kafil, H; Mirshafiey, A; Yousefi, M (Cellular and Molecular Biology, 2016)
Inflammation is inseparable part of different diseases especially cancer and autoimmunity. During inflammation process toll like receptor 4(TLR4) responds to lipopolysaccharide (LPS), one of the bacterial components, and TLR4 signaling leads to interleukine-1 receptor associated kinase-1 (IRAK1) and tumor necrosis factor (TNF) receptor associated factor6 (TRAF6) activation which ultimately results in nuclear factor- Ä¸B (NF-Ä¸B) activation as the main transcription factor of inflammatory cytokines. Conversely, NF-Ä¸B over activation induces miR-146a in innate immune cells which can consequently reduce TRAF6, IRAK1, and NF-Ä¸B activation in a negative feedback. G2013 is a novel designed non-steroidal anti-inflammatory drug (NSAID) which was recently shown to be effective in experimental autoimmune encephalomyelitis (EAE) mouse model. The aim of this study was to evaluate G2013 effects on inflammatory (IRAK1 and TRAF6) and anti-inflammatory (miR-146a) factors of TLR4 signaling pathway. For this purpose, cytotoxicity of G2013 has been evaluated by MTT assay. Expression level of miR-146a in PBMCs and IRAK1 along with TRAF6 in HEK-293 TLR4 cells have been determined using real time PCR. Our results showed that IC50 of G2013 was 25Î¼g/ml, thus 5 and 25 Î¼g/ml concentrations used for further treatments as low dose and high dose concentrations. Our results showed that IRAK1 expression reduced between 5 to 8 fold after treatment by G2013 in a dose dependent manner (p<0.001). In parallel TRAF6 expression declined between 3 to 10 fold dose dependently (p<0.05). However, miR-146a expression was not affected after treatment with low dose and high dose of G2013. In conclusion our data showed that G2013 can regulate TLR4 signaling pathway during inflammation by reducing downstream signaling molecules, IRAK1 and TRAF6 without altering miR-146a expression.